If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -7x = 109 + -28x Solving 13 + -7x = 109 + -28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28x' to each side of the equation. 13 + -7x + 28x = 109 + -28x + 28x Combine like terms: -7x + 28x = 21x 13 + 21x = 109 + -28x + 28x Combine like terms: -28x + 28x = 0 13 + 21x = 109 + 0 13 + 21x = 109 Add '-13' to each side of the equation. 13 + -13 + 21x = 109 + -13 Combine like terms: 13 + -13 = 0 0 + 21x = 109 + -13 21x = 109 + -13 Combine like terms: 109 + -13 = 96 21x = 96 Divide each side by '21'. x = 4.571428571 Simplifying x = 4.571428571
| (4x-6)+(5x+7)= | | =(4x-6)+(5x+7) | | 17+2n=87 | | (b+4)(2b-5)=0 | | X-2(-1)=6 | | 4(2y+3)-5(y+3)= | | x*2x+x*10= | | 58-2x=10x+22 | | 118-6x=10x-22 | | .38x+.44(7)=.40(x+7) | | 116-3x=15x+24 | | 5x+7=-38-10x | | 8+3x=128 | | -12-9x=27-16x | | 95-3x=4x+11 | | -12m-37(12n+8m)= | | -7-7x=8x+23 | | 25x-1=65 | | 4(3r-2)=-3(r+7) | | 5x+5=95-5x | | 6x+7=-121-10x | | 8x+6=30 | | 3p(2p-4)-2p(3p+4)= | | 1=35-5(x+3) | | 104-6x=3x+5 | | 2x-1=9x-78 | | -20-3x=12-7x | | 2x-1=9-78 | | 4x+39=12x-25 | | 6x+6=90-6x | | 2x-y=y | | .2x+.4(5)=.3(x+2) |